Overcoming Resource Constraints on Product Innovation by Recruiting Talent From Rivals: A Study of the Mutual Fund Industry, 1986–1994 - Rao, Hayagreeva; Drazin, Robert (Academy of Management Journal, 2002)
Although recruitment is a practical strategy young and poorly connected firms can use to overcome constraints on product innovation, it has received little attention. Younger firms and poorly connected firms have lower rates of product innovation than their advantaged counterparts and recruit more from rivals to surmount resource constraints. Younger firms recruit veterans, and poorly connected firms poach from large firms. However, recruit characteristics have stronger effects on product innovation in poorly connected organizations.